2021
DOI: 10.14744/tjtes.2021.97760
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rutin on experimentally induced acute heart contusion in rats. Biochemical and histopathological evaluation

Abstract: BACKGROUND: Acute cardiac contusion induced by trauma is known with its high mortality and morbidity. The role of oxidative stress and inflammation in its pathophysiology has led to the investigation of antioxidant and anti-inflammatory substances in non-surgical treatment. In this study, the effects of rutin which has these two features on acute cardiac contusion were investigated. METHODS: Thirty male albino Wistar rats were divided into three equal groups as healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Also, they reported on the cardioprotective mechanisms of RTN, particularly in cardiac hypertrophy. On the other hand, treated with RTN caused inhibiting the apoptosis of cardiomyocytes and improving cardiac function and related to the restoration of the structure and function of myocardial mitochondria [1], reduce cardiomyocyte damage [34], and it may be protecting cardiac tissue from oxidative damage due to the anti-inflammatory effect associated with the inhibition of interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Also, they reported on the cardioprotective mechanisms of RTN, particularly in cardiac hypertrophy. On the other hand, treated with RTN caused inhibiting the apoptosis of cardiomyocytes and improving cardiac function and related to the restoration of the structure and function of myocardial mitochondria [1], reduce cardiomyocyte damage [34], and it may be protecting cardiac tissue from oxidative damage due to the anti-inflammatory effect associated with the inhibition of interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) [14].…”
Section: Discussionmentioning
confidence: 99%
“…These results were confirmed by previous studies that showed that treatment with rutin in tissues can prevent and inhibit lung infections. a study of Elma et al (2022) explained the effect of rutin on blunt trauma pulmonary contusion in mice and how it reduced and improved the effects on lung tissue and contributed to its treatment.…”
Section: Histological Studymentioning
confidence: 99%
“…These results were confirmed by previous studies that showed that treatment with rutin in tissues can prevent and inhibit lung infections. a study of Elma et al (2022) explained the effect of rutin on blunt trauma pulmonary contusion in mice and how it reduced and improved the effects on lung tissue and contributed to its treatment.…”
Section: Histological Studymentioning
confidence: 99%